Parallel genetic and phenotypic differentiation of Erigeron annuus invasion in China - Liu, Yuan-Yuan; Yang, Qin-Fen; Li, Zhen; Zhou, Zhi-Xiang; Shi, Xue-Ping; Wang, Yong-Jian (Frontiers in Plant Science, 2023)
What determines the growth and spread advantages of an alien plant during the invasion process remains open to debate. Genetic diversity and differentiation of an invasive plant populations might closely relate with its growth adaptation and spread in introduced range. However, still little is known about whether phenotypic and genetic variation of invasive plant populations co-vary in invasion process along invaded geographic distance. In a wild experiment, we examined genetic variation of populations of a worst invasive species, Erigeron annuus, in different geographical distances to the first recorded point of introduction (FRPI) in China. We also measured the growth traits and the coefficient of variation (CV) of populations in the wild and in a common garden experiment. We found that E. annuus populations had better growth performance (i.e. height and biomass) and genetic diversity, and less variation of the traits and genetic differentiation in long-term introduced (east) than in short-term introduced (west) region. Furthermore, population growth performance was significantly positive or negative correlation with genetic diversity or with genetic differentiation. Our results indicated that parallel genetic and phenotypic differentiation along invaded geographic distance in response to adaptation and spread, and populations entered earlier in the introduced regions had consistent high genetic diversity and high growth dominance. Grow and reproductive traits can be used as significant predictor to the adaptation and genetic variation of invasive plants